2022
DOI: 10.1021/acs.joc.2c00825
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a Supramolecular Brønsted Acid Catalyst Based on the Noria Macrocycle

Abstract: The synthesis of derivatives of the Noria macrocycle and the structurally similar macrocycle, R3, each containing 12 sulfonic acid groups, is reported. Herein, we demonstrate their utility as reusable Brønsted acid catalysts for the Biginelli synthesis of dihydropyrimidinones and the Pechmann synthesis of coumarins. We also demonstrate that the supramolecular structure directs the reagents to interact with the sulfonic acid catalytic sites, thus increasing the catalyst’s efficiency compared to other monomeric,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The synthesis of R3-Noria-MeSO 3 H was performed similarly to the previously reported procedure 33 and is described in Supporting Information (S1). The 5 mM, 2.5 mM, 1 mM, 0.5 mM, 0.1 mM, 0.05 mM, 0.01 mM, 5 μM, and 1 μM solutions of R3-Noria-MeSO 3 H in deionized water (DI H 2 O), phosphate buffer saline (PBS), and saline were prepared using the procedure described in Supporting Information (S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of R3-Noria-MeSO 3 H was performed similarly to the previously reported procedure 33 and is described in Supporting Information (S1). The 5 mM, 2.5 mM, 1 mM, 0.5 mM, 0.1 mM, 0.05 mM, 0.01 mM, 5 μM, and 1 μM solutions of R3-Noria-MeSO 3 H in deionized water (DI H 2 O), phosphate buffer saline (PBS), and saline were prepared using the procedure described in Supporting Information (S2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…31 Unfortunately, Noria and its recently discovered isomer R3, 32 which is easier to synthesize and purify, are not water-soluble and are sparingly soluble in all common organic solvents except DMSO. Herein, we demonstrated that novel watersoluble resorcinarene trimer (R3) methanesulfonate (R3-Noria-MeSO 3 H), 33 Noria, produces a superior HyperCEST effect in aqueous solutions. We investigated the dependence of the R3-Noria-MeSO 3 H HyperCEST effect on the presence of dissolved inorganic salts in a solution.…”
mentioning
confidence: 99%